The effects of the physical procedures in patients with diabetic neuropathy - Grbović, Vesna; Stefanović, Srdjan; Djukić, Svetlana; Nurković, Jasmin; Zdraković Petrović, Natasa; Parezanović Ilić, Katarina; Divjak, Ana S; Jurišić Škevin, Aleksandra (Vojnosanitetski pregled, 2021)
Abstract Background/Aim. Neuropathy represents the most frequent complication in the patients with diabetes mellitus (DM). Symmetric distal sensorimotor polyneuropathy (DSP), which represents the most frequent type of diabetic neuropathy, is present in 30% of hospitalized diabetic patients. The aim of our study was to compare the effects of physical therapy (PT) and alpha-lipoic acid (ALA) supplementation on pain reduction and quality of life improvement in the DSP patients. Methods. The study was performed on 60 adult patients with DM type 2 and DSP. The patients were randomly divided into 2 groups: group A (n = 30) was treated by PT and group B (n = 30) was treated by ALA. The study lasted 6 months during which 3 diagnostic-therapeutic cycles were performed. To asses their pain before and after every of 3 cycles, we used visual analog scale (VAS). We also evaluated quality of life before the 1st and after the 3rd cycle with the European Quality of Life Questionnaire (EQ-5D-3L). To analyze results between groups we used mixed between-within subjects ANOVA and statistical significance was set on p < 0.05. Results. Pain intensity showed statistically significant influence of both PT and ALA (λ = 0.028; p < 0.001). A statistically significant difference between the effects of those two therapy modalities was observed (F = 4.78; p < 0.05): PT reduced pain to the greater extent than ALA. A statistically significant improvement was found in the domain of pain/discomfort both in the group A (η = 0.54, p < 0.001) and group B (η = 0.57, p < 0.001), as well as anxiety/depression (group A: η = 0.32, p = 0.008; group B: η = 0.22, p < 0.019) and EQ-VAS (both groups, p < 0.05). Conclusion. Our research showed that physical therapy had a greater influence in pain reduction than alpha-lipoic acid in the patients with DSP.
Keywords: diabetic neuropathies; physical therapy modelaties; treatment outcome